Utility of shock index to predict mortality risk in decompensated heart failure - Amanda Naidoo-Pillay; Suma Rajan; Andreas Engelbrecht (Journal of the Colleges of Medicine of South Africa, 2025)
Background: Decompensated heart failure (HF) is a serious condition that requires rapid evaluation and treatment. Shock index (SI) is a bedside predictor tool used to identify risk of mortality and morbidity.